Biology : - Campbell, Neil A. (Benjamin Cummings, 1997)
This is an introductory biology text for non-biology majors, designed to help students understand important concepts and make connections. The unifying theme of evolution helps offer a historical view of biology. The integrated art and text programme is designed to teach fundamental concepts in a clear and uncluttered manner and examples illustrate biological concepts and connect to the everyday world. The book emphasizes sciences as a process through its use of examples, key experiments and historical development of theories.